2018
DOI: 10.1111/add.14464
|View full text |Cite
|
Sign up to set email alerts
|

Electronic nicotine delivery system (ENDS) use in relation to mental health conditions, past‐month serious psychological distress and cigarette smoking status, 2017

Abstract: Background and Aims: Adults with mental health conditions (MHC) exhibit disproportionately high smoking prevalence and experience profound tobacco-related disparities. U.S. nationally representative surveys from 2012-2015 found relatively high usage of electronic nicotine delivery systems (ENDS; e.g., e-cigarettes) among adults with MHC. However, research has not examined these associations specifically among never smokers. Aims were to examine associations among MHC diagnosis, serious psychological distress (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 74 publications
(80 reference statements)
1
22
0
Order By: Relevance
“…This is a persistent issue which has not only been found in mental healthcare, but also among healthcare professionals who work with other socially disadvantaged groups experiencing high smoking prevalence, including those in addiction services and the homeless ( Cookson et al, 2014 ; Garner & Ratschen, 2013 ). Interestingly, these socially disadvantaged smokers are often just as motivated to quit compared to the general population, and interest in EC and experimentation are common among these smokers ( Dawkins et al, 2019 ; Hefner, Valentine, & Sofuoglu, 2017 ; Spears et al, 2018 ). However, smoking prevalence remains disproportionately higher in these groups, suggesting that these smokers are lacking the support required to convert exclusively to ECs.…”
Section: Discussionmentioning
confidence: 99%
“…This is a persistent issue which has not only been found in mental healthcare, but also among healthcare professionals who work with other socially disadvantaged groups experiencing high smoking prevalence, including those in addiction services and the homeless ( Cookson et al, 2014 ; Garner & Ratschen, 2013 ). Interestingly, these socially disadvantaged smokers are often just as motivated to quit compared to the general population, and interest in EC and experimentation are common among these smokers ( Dawkins et al, 2019 ; Hefner, Valentine, & Sofuoglu, 2017 ; Spears et al, 2018 ). However, smoking prevalence remains disproportionately higher in these groups, suggesting that these smokers are lacking the support required to convert exclusively to ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Vaping is associated with blue-collar workers (Eichler et al, 2016). Research indicates those reliant on Medicaid, state assistance, or uninsured were more likely to vape (Spears et al, 2019). Vaping is predominately associated with Whites and Hispanics, while Blacks and Asians had lower rates (Bostean et al, 2015; Spears et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research indicates those reliant on Medicaid, state assistance, or uninsured were more likely to vape (Spears et al, 2019). Vaping is predominately associated with Whites and Hispanics, while Blacks and Asians had lower rates (Bostean et al, 2015; Spears et al, 2019). In addition, research has indicated that 40% of those who vape were not prior cigarette users (Cheney et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular aspects of THR in mental health patients include a high prevalence of smoking and use of ENDS, 75,76,77 preliminary evidence that ENDS are highly effective for smoking cessation in this group, 76 and that patients with mental health issues may be more prone to addiction 78,79 and struggle to quit nicotine in the longer term. 75 Furthermore, nicotine itself may have an impact on symptoms and progression of the mental health condition. 80 Seven studies investigating mental health outcomes were identified in this review, but there were others reporting on mental health disease as a predictor of ENDS use.…”
Section: Mental Healthmentioning
confidence: 99%